Community-Based Empowerment Intervention to Strengthen Maternal Health Behavior: A Quasi-Experimental Study - Sri Wahyuni; Dewi Umbarsari; Ria Wahyuni; Rika Riyandani; Asridawati Akib (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2026)
Maternal health behavior is a key determinant in reducing maternal and child mortality and improving overall family health. Although various health programs have been implemented through primary healthcare services, improvements in maternal health behavior remain suboptimal. Therefore, a community-based empowerment approach involving families, community health volunteers, and the broader community is needed. Objective: This study aimed to analyze the effectiveness of a community-based empowerment intervention in strengthening maternal health behavior in the working area of Tamalanrea Jaya Primary Health Center, Makassar, Indonesia. Methods: This quantitative study employed a quasi-experimental pretest-posttest control group design. A total of 52 respondents were recruited using purposive sampling and assigned to an intervention group 26 and a control group 26. The intervention was implemented over eight weeks through health education, community health volunteer mentoring, group discussions, and home visits. Data were collected using a validated and reliable maternal health behavior questionnaire. Data analysis included univariate and bivariate analyses. The Shapiro-Wilk test indicated that all variables were normally distributed (p > 0.05); therefore, Paired Sample t-test and Independent Sample t-test were used for statistical analysis. Results: The mean maternal health behavior score in the intervention group increased significantly from 61.38 ± 7.42 at baseline to 82.54 ± 6.15 after the intervention (p < 0.001), whereas no significant improvement was observed in the control group (p = 0.083). Furthermore, a significant difference in post-intervention maternal health behavior scores was found between the intervention and control groups (p < 0.001). Conclusion: Community-based empowerment interventions are effective in improving maternal health behavior and have the potential to serve as a promotive and preventive strategy to support efforts to reduce maternal mortality through strengthening primary healthcare services.